2014
DOI: 10.4174/astr.2014.86.3.136
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free DNA as a promising biomarker in patients with gastric cancer: diagnostic validity and significant reduction of cfDNA after surgical resection

Abstract: PurposeThe aim of this study is to determine whether levels of circulating free DNA (cfDNA) increase according to cancer progression, whether they are restored after surgical resection, and to evaluate cfDNA in gastric cancer patients as a useful biomarker.MethodsA case-control study design was used. Thirty gastric cancer patients and 34 healthy subjects were enrolled from two hospitals in South Korea. The plasma cfDNA of patients with gastric cancer were obtained before surgery and 24 hours after surgery, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 24 publications
(26 reference statements)
2
81
1
5
Order By: Relevance
“…The cfDNA in plasma from patients with cancer originates from normal nonmalignant cells, as well as necrotic and apoptotic tumor cells; but neither the origin nor the fate of the circulating DNA is fully understood [39,[50][51][52]. A previous study has shown a correlation between quantitative cfDNA levels and tumor-specific KRAS and EGFR mutations in plasma, which triggered us to hypothesize that increasing levels of cfDNA in patients with cancer are primarily of tumor origin [44,[53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…The cfDNA in plasma from patients with cancer originates from normal nonmalignant cells, as well as necrotic and apoptotic tumor cells; but neither the origin nor the fate of the circulating DNA is fully understood [39,[50][51][52]. A previous study has shown a correlation between quantitative cfDNA levels and tumor-specific KRAS and EGFR mutations in plasma, which triggered us to hypothesize that increasing levels of cfDNA in patients with cancer are primarily of tumor origin [44,[53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years cell-free DNA (cfDNA) has become increasingly used as a clinical and noninvasive biomarker in the fields of cancer [13], pre-natal diagnostics [4], organ transplantation [5], and in several emergency conditions [68]. cfDNA, defined as extracellular DNA circulating freely in the blood, can be further subcategorized to circulating mitochondrial DNA (mtDNA) and circulating nuclear DNA (nDNA).…”
Section: Introductionmentioning
confidence: 99%
“…Several reported studies showed significant differences in the amounts of plasma DNA isolated from healthy individuals, patients with benign disease, and cancer patients. Although some studies revealed significantly higher concentrations of cfDNA in cancer patients and that simple quantification of cfDNA can confirm the presence of cancer or disease-free status and relapse after curative surgery (40,41 ), numerous other studies demonstrate that solely the amount of cfDNA is not a useful diagnostic tool and that the utility of cfDNA is limited without knowledge of tumor mutations (42,43 ). A study that analyzed total plasma DNA concentrations and tumorspecific KRAS mutations in CRC patients showed that a higher amount of tumor-specific fragments and that a higher number of CTCs were linked to biphasic size distributions of plasma DNA fragments (Fig.…”
Section: Cfdna As a Diagnostic Biomarkermentioning
confidence: 99%